[Western Australia 1:50 000 photomosaic series]. 1751-11,. Mia Mia - Western Australia. Department of Lands and Surveys ([Perth] : Dept of Lands and Surveys, 1976)
"A semi-controlled mosaic compiled in the format of the 1:50 000 national series (A.G.D.) from aerial photography".
Keywords: Mia Mia (W.A.) -- Maps; Remote-sensing maps